Antimicrobial Activity of Black Cumin Extracts (Nigella sativa) Against Food Pathogenic and Spoilage Bacteria - SEDARNAWATI YASNI; ELVIRA SYAMSIR; EVA H DIREJA (Microbiology Indonesia, 2009)
This study aimed to analyze the antimicrobial activity of black cumin (Nigella sativa) extracts in inhibiting the growth of pathogenic and spoilage bacteria. Black cumin was extracted by using steam distillation, single solvent extraction, and continuous solvent extraction. Ethanol extract was the best extract in inhibiting the growth of bacteria while both aqueous and hexane extracts were less effective as antimicrobial agents. Ethanol extract, essential oil, and ethyl acetate extract have a broad antimicrobial spectrum. The chemical composition of the essential oil was analyzed using a GC-MS technique. The major component of black cumin essential oil was para-cymene, followed by trans-anethole, alloaromadendrene, á-thujene, and thujyl alcohol along with many other components in minor amounts. The Minimum Inhibitory Concentration (MIC) value ofethanol extract in inhibiting the growth of Salmonella typhimurium was 0.084% (w/w), of essential oil in inhibiting the growth of Bacillus cereus was 1.72% (w/w), of ethyl acetate extract in inhibiting the growth of Staphylococcus aureus was 1.88% (w/w) and of methanol extract in inhibiting the growth of Pseudomonas aeruginosa was 1.88% (w/w).